Rbfox proteins regulate tissue-specific alternative splicing of Mef2D required for muscle differentiation - Runfola, Valeria (J Cell Sci, 2015)
Among the Mef2 family of transcription factors, Mef2D is unique in that it undergoes tissue-specific splicing to generate an isoform that is essential for muscle differentiation. However, the mechanisms mediating this muscle-specific processing of Mef2D remain unknown. Using bioinformatics, we identified Rbfox proteins as putative modulators of Mef2D muscle-specific splicing. Accordingly, we found direct and specific Rbfox1 and Rbfox2 binding to Mef2D pre-mRNA in vivo. Gain- and loss-of-function experiments demonstrated that Rbfox1 and Rbfox2 cooperate in promoting Mef2D splicing and subsequent myogenesis. Thus, our findings reveal a new role for Rbfox proteins in regulating myogenesis through activation of essential muscle-specific splicing events.